Managing hip pain in the athlete - Prather, H.; Colorado, B.; Hunt, D. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
Hip and groin pain is commonly experienced by athletes. The differential diagnosis should include both intra-articular and extra-articular sources for pain and dysfunction. A comprehensive history and physical examination can guide the evaluation of hip pain and the potential need for further diagnostics. Treatment of athletes with hip disorders includes education, addressing activities of daily living, pain-modulating medications or modalities, exercise and sports modification, and therapeutic exercise. Surgical techniques for prearthritic hip disorders are expanding and can offer appropriate patients a successful return to athletic endeavors when conservative measures are not effective.